A Three Decades Assessment of Forest Cover Changes in The Mountainous Tropical Forest of Timor Island, Indonesia - Eko Pujiono; Ronggo Sadono; Hartono Hartono; Muhammad Ali Imron (Jurnal Manajemen Hutan Tropika, 2019)
The Mutis Timau Forest Complex (MTFC), a remained mountainous tropical forest area in Timor Island, located in Indonesia and Timor-Leste border region, tends to decrease gradually. Unfortunately, declined forest area and their rates are not explained by reliable spatial and quantitative information. This study attempts to assess the extent and rate of forest cover changes in the MTFC during the last 30 years. We used Landsat images on three different dates: 1987, 1999, and 2017. Then, we applied a hybrid classification approach that combines the application of Forest Canopy Density model-obtained from four biophysical indices and supervised classification-maximum likelihood classification to generate land cover maps. Finally, we detected forest cover change by comparing land cover map in different years. Results illustrated that the extent and annual rate of deforestation, forest degradation, forest regrowth, and afforestation during 1987–2017 were 2,232 ha (0.36%), 4,820 ha (1.10%), 1,475 ha (0.69%), and 1,252 ha (0.40%), respectively. Such results are important for the MTFC authority to establish appropriate plan and strategies in forest management activities and can be used to support some policies/programs for combating deforestation and forest degradation.